Uptake of glucose-conjugated MGMT inhibitors in cancer cells: role of flippases and type IV P-type ATPases. Issue 1 (December 2017) - Tomaszowski, Karl-Heinz; Hellmann, Nadja; Ponath, Viviane; Takatsu, Hiroyuki; Shin, Hye-Won; Kaina, Bernd
Abstract The DNA repair proteinO 6 -methylguanine-DNA-methyltransferase (MGMT) is a key determinant of cancer resistance. The MGMT inhibitorsO 6 -benzylguanine (O6 BG) andO 6 -(4-bromothenyl)guanine (O6 BTG) failed to enhance the therapeutic response due to toxic side effects when applied in combination with alkylating chemotherapeutics, indicating a need of inhibitor targeting. We assessed MGMT targeting that relies on conjugating the inhibitors O6 BG and O6 BTG to ß-D-glucose, resulting in O6 BG-Glu and O6 BTG-Glu, respectively. This targeting strategy was selected by taking advantage of high demand of glucose in cancers. Contrary to our expectation, the uptake of O6 BG-Glu and O6 BTG-Glu was not dependent on glucose transporters. Instead, it seems that after membrane binding the conjugates are taken up via flippases, which normally transport phospholipids. This membrane binding is the consequence of the amphiphilic character of the conjugates, which at higher concentrations lead to the formation of micelle-like particles in aqueous solution. The unusual uptake mechanism of the conjugates highlights the importance of proper linker selection for a successful ligand-based drug delivery strategy. We also demonstrate that proteins of the P4-Type ATPase family are involved in the transport of the glucose conjugates. The findings are not only important for MGMT inhibitor targeting, but also for other amphiphilic drugs.